Upaya Madrasah dalam Menjaga Kedisiplinan Ibadah Shalat Fardhu Zhuhur: Studi Kasus di MTs. S Baitur Rahman Parau Sorat Kabupaten Padang Lawas Utara - Siagian, Desram; Nasution, Abdusima; Dalimunthe, Latifah Annum; Amin, Muhammad; Fata, Nahriyah (PT. Student Rihlah Indonesia, 2025)
This study aims to describe the efforts made by the madrasah in maintaining the discipline of the implementation of the Fardhu Zhuhur prayer at MTs. S Baitur Rahman Parau Sorat, Batang Onang District, North Padang Lawas Regency. This study uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation. The data obtained was analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that madrasas carry out various coaching strategies, such as routine scheduling of congregational prayers, active involvement of teachers in supervision and coaching, and habituation of a religious environment. In addition, madrassas also provide spiritual motivation to students through religious activities. The obstacles faced include the lack of awareness of some students and the limited worship support facilities. Overall, the efforts made by the madrasah are quite effective in fostering student discipline in carrying out obligatory prayers in congregation.